Cytochrome P450 genes from the aquatic midge Chironomus tentans: Atrazine-induced up-regulation of CtCYP6EX3 enhanced the toxicity of chlorpyrifos. (November 2017) - Tang, Guanghui; Yao, Jianxiu; Li, Daqi; He, Yanping; Zhu, Yu-Cheng; Zhang, Xin; Zhu, Kun Yan
Abstract: The open reading frames of 19 cytochrome P450 monooxygenase ( CYP ) genes were sequenced from Chironomus tentans, a commonly used freshwater invertebrate model. Phylogenetic analysis of the 19 CYPs along with a previously reported CYP ( CtCYP4G33 ) revealed that they belong to three different clans, including 3 in CYP4, 15 in CYP3, and 2 in mitochondria clan. When third-instar larvae were exposed to atrazine at 5000 μg/L, the transcription of CtCYP6EX3, CtCYP6EV3, CtCYP9AT1 and CtCYPEX1 was significantly up-regulated. To examine whether CtCYP6EX3 played a role in oxidative activation of chlorpyrifos to chlorpyrifos-oxon, we evaluated larval susceptibility to chlorpyrifos after CtCYP6EX3 transcript was suppressed by RNAi. The larvae fed chitosan/ds CtCYP6EX3 nanoparticles showed a significantly decreased CtCYP6EX3 transcript (53.1%) as compared with the control larvae fed chitosan/ds GFP nanoparticles. When the CtCYP6EX3 -silenced larvae were exposed to chlorpyrifos at 6 μg/L or its binary mixture with atrazine (chlorpyrifos at 3 μg/L and atrazine at 1000 μg/L), the larvae became less susceptible to the pesticides as their mortalities decreased by 24.1% and 20.5%, respectively. These results along with our previous findings suggested that the increased toxicity of chlorpyrifos was likely due to an enhanced oxidative process from chlorpyrifos to chlorpyrifos-oxon by CtCYP6EX3 as RNAi of CtCYP6EX3 led to decreased susceptibility of C. tentans larvae to chlorpyrifos alone and the binary mixture of atrazine and chlorpyrifos. However, further study would be necessary to validate our results by functional assays using heterologously expressed CtCYP6EX3 enzyme. Graphical abstract: Highlights: Open reading frames of 19 cytochrome P450 genes were sequenced from C. tentans . Atrazine up-regulated CtCYP6EX3, CtCYP6EV3, CtCYP9AT1 and CtCYPEX1 expressions. Chitosan/dsRNA nanoparticle-based RNAi was used to study the function of CtCYP6EX3 . Atrazine-induced up-regulation of CtCYP6EX3 enhanced the toxicity of chlorpyrifos.